The prognosis of acute symptomatic seizures after ischaemic stroke. Issue 1 (27th January 2016) - Leung, Thomas; Leung, Howan; Soo, Yannie O Y; Mok, Vincent C T; Wong, K S
Abstract : Objective: Acute symptomatic seizure (AS) after ischaemic stroke is defined as a seizure occurring ≤7 days of the stroke. There remains a lack of information on the prognosis of AS after ischaemic stroke and how it should be treated. Methods: We prospectively recruited patients after their incidents of ischaemic stroke from a population-based stroke registry. Stroke aetiology was defined according to Trial-of-ORG-10172 in acute-stroke treatment (TOAST). Patients were examined for any transient complete-occlusion with recanalisation (TCOR) and haemorrhagic transformation. The seizure outcomes were (1) acute clustering of seizures ≤7 days, (2) seizure recurrence associated with stroke recurrence beyond the 7-day period and (3) unprovoked seizure (US) >7 days. Results: 104 patients (mean age 65 years/55% female) with AS after ischaemic stroke were identified (mean follow-up 6.17 years). Comparison of the group of patients with AS and those without seizures showed that patients with AS had significantly less large-vessel and small-vessel disease but more cardioembolisms (p<0.05) and a higher proportion of TCOR (p<0.01), multiple territory infarcts (p=0.007) and haemorrhagic transformations (p<0.01). Using Kaplan–Meier statistics, the risk of acute clustering of seizures ≤7 days was 22%, with a statistical trend for TCOR as a predictive factor (p=0.06). The risk of seizure recurrence associated with worsening/recurrence of stroke beyond 7 days was 13.5% at 2 years, 16.4% at 4 years and 18% at 8 years. Presence of >2 cardiovascular risk factors (p<0.05) and status epilepticus (P<0.05) are predictive risk factors on Cox regression model. The risk of US was 19% at 2 years, 25% at 4 years and 28% at 8 years with epileptiform EEG as a predictive factor (p<0.05). Conclusions: Seizure recurrence following AS after ischaemic stroke may appear as acute clustering. Afterwards, seizures may occur as often with a recurrent stroke as without one within 4.2 years. We recommend the use of antiepileptic agents for up to 4 years if the underlying stroke aetiology cannot be fully treated.